Analysis of "Goboy" Traditional Games on Fundamental Basic Movements of SD Laboratory UNP Kediri Students - Amri Irawan Saputra; M. Anis Zawawi; Weda (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
This research was carried out with the findings and observers in the field of sports and health physical education, which defines that many of the learning processes carried out in physical education are still not running effectively. So it is necessary to increase their ability when implementing learning in schools, one of which is by making new innovations in traditional games to improve students' basic fundamental movement skills which are carried out in ongoing learning. The data collection techniques used in this study were: observation, interviews, and documentation. This research was carried out at SD Laboratory UNP Kediri, Mojoroto District, Kediri City. Collecting data in this study uses an instrument in the assessment of ongoing learning. Through analysis on the implementation of learning related to basic fundamental movement skills, data was obtained showing that in learning basic fundamental movements through traditional goboy game media as many as 35 upper class students at SD Laboratory UNP Kediri produced good value categories with existing percentages for basic fundamental movements (motion locomotor, nonlocomotor, and manipulative). This shows that the traditional goboy game can raise students' basic fundamental movement skills in this learning